2014
DOI: 10.1017/s0008423914000754
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Public Opinion about the Military: Assessing the Influences on Attitudes toward Defence Spending and Participation in Overseas Combat Operations

Abstract: What are the influences on Canadians' preferences about defence spending and the use of military force? Despite more than a decade of heightened defence spending and active fighting in the War on Terror in Afghanistan, the longest combat operation in the history of the Canadian Forces, we do not know enough about how Canadians' sociodemographic characteristics and attitudes may influence their views about taking part in overseas combat operations and funding the institution charged with carrying out these dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Do Canadian political leaders influence the public's views on the legitimate use of force, either by their support for particular missions or by the arguments they raise (Nossal, 2013)? Do partisans have different approaches towards the legitimate use of force (Fitzsimmons et al, 2014; Gravelle et al, 2014), with Conservatives—as might be imagined—more tempted towards a continentalist foreign policy? An analysis of the party-political dimensions of Canadians’ attitudes towards peace operations was not possible with these data, but future work would do well to examine it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Do Canadian political leaders influence the public's views on the legitimate use of force, either by their support for particular missions or by the arguments they raise (Nossal, 2013)? Do partisans have different approaches towards the legitimate use of force (Fitzsimmons et al, 2014; Gravelle et al, 2014), with Conservatives—as might be imagined—more tempted towards a continentalist foreign policy? An analysis of the party-political dimensions of Canadians’ attitudes towards peace operations was not possible with these data, but future work would do well to examine it.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other studies have focused on Canadian views on specific missions, such as series of peacekeeping missions (Martin and Fortmann, 1995) or the wars in Afghanistan and Iraq (Fitzsimmons et al, 2014; Massie, 2008; Massie et al, 2010). However, examining opinion about particular missions is somewhat problematic as an indicator of more general features of public opinion.…”
Section: Methodsmentioning
confidence: 99%
“…In Canada, partisan differences in foreign policy opinions emerged most clearly in the late 1980s over the issue of free trade with the US, which dominated the 1988 federal election campaign (Johnston et al, 1992: 155). More recently, studies have found differences between Conservative partisans and supporters of other parties, especially on military and defence issues (Fletcher et al, 2009; Fitzsimmons et al, 2014; Gravelle et al, 2014). It is less obvious why these partisan differences exist.…”
Section: Conceptual and Methodological Considerationsmentioning
confidence: 99%
“…It is less obvious why these partisan differences exist. They may represent distinctive underlying political orientations and ideologies that lead citizens to support different political parties (Gravelle, 2014; Fitzsimmons et al, 2014)—in the case of Brexit, for instance, convictions on the importance of British political traditions or the benefits of multilateral cooperation. It is also possible, however, that partisan differences emerge simply because of citizens’ lack of engagement with, and awareness of, international affairs.…”
Section: Conceptual and Methodological Considerationsmentioning
confidence: 99%
“…13Leal 2005; Simon and Lovrich 2010; Eichenberg and Stoll 2012; Fitzsimmons, Craigie and Bodet 2014.…”
mentioning
confidence: 99%